Family marginalization, alienation, and estrangement: questioning the nonvoluntary status of family relationships. Issue 1 (2nd January 2017) - Scharp, Kristina M.; Dorrance Hall, Elizabeth
ABSTRACT: Despite assumptions that families are close and intact, the prevalence of family member marginalization, parent–child alienation, and parent–child estrangement is overwhelming. Largely ignored by the research community, these three family distancing processes pose significant disruptions to the entire family system. Although some of associated behaviors lead to turmoil and decreased well-being, distancing can also be a healthy solution to an unhealthy environment. This manuscript traces the history of these three processes; offering conceptualizations, strengths, and critiques of each perspective. Specifically, we discuss the way communication researchers have influenced these processes as well as how they can contribute to this sparse body of research in the future. Finally, we compare the processes and question whether families should be considered nonvoluntary.